Mental Health Implication of Quarantine and Isolation on Children and Adolescents during Covid-19 Outbreak: A Narrative Review - Rezky Aulia Yusuf (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2020)
Quarantine and isolation are approaches that often used to prevent and control the transmission to the population at risk. These approaches limit the social interaction, confined mobility and daily activities of the pretentious individual. Those complete change to the psychosocial environment and have the potential to threaten the mental health of children and adolescents significantly. This literature review purposed to describe and summarize the available evidence on mental health problems caused by quarantine and isolation on child and adolescent during Covid-19 pandemic. A literature search was conducted using three major database; PubMed, Google scholar and SAGE journals. Including papers that systematically conducted reviews and reported mental health problems among children and teenagers during COVID-19 outbreak. Among 743 journal articles, only 5 met all inclusions criteria. These articles reported a high burden of mental disorders among children and adolescents. Prevalent of psychological problems among the affected individuals include fear, loneliness, depression, anxiety, mood disorders, insomnia, and other adverse negative emotions. There are many mental health threats associated with the pandemic and subsequent restrictions. Child and adolescent psychiatrists and parents must ensure continuity of care during all phases of the pandemic. Research is needed to assess the implications of policies on mental health of children and adolescents in order to be better prepared for future developments.